Tracing the motivation to innovate: A study of grassroot innovators in India - Saradindu Bhaduri; Hemant Kumar (Max Planck Institute of Economics, 2009)
Extrinsic motivations like intellectual property protections and fiscal incentives continue to occupy the centre stage in debates on innovation policies. Joseph Schumpeter had, however, argued that the motive to accumulate private property can only explain part of innovative activities. In his view, the joy of creating, of getting things done associated with the behavioural traits that seek out difficultiesand takes delight in ventures stand out as the most independent factor of behaviour in explaining the process of economic development, especially in early capitalist societies. Taking the case of 'grassroot' innovators in India, we re-examine the motivations behind innovative behaviour. We draw upon the literature on effectance motivation theory to construct operational indicators of extrinsic and intrinsic motivations. Interestingly, we find that pure extrinsic forms of motivation drive only a fraction of individual innovative behaviour. Also, importance of intrinsic motivation in guiding innovative behaviour is found to high when uncertainty is high. We accordingly draw a few policy implications.
Keywords: 330; Motivation; Grassroot Innovation; India